Sistema de Ajuste Automático de Bitola para Tratores Agrícola de Esteiras - Bezerra, José Heldenir Pinheiro (2018)
The current scenario of the agricultural machinery industry has incorporated new technologies through the use of specific software and equipment to replace traditional operations performed by conventional machines and human hands. The option to use the soil preparation or planting system does not follow pre-established rules, the farmer must make decisions based on several aspects present in his property, such as: soil type, slope of the land, rainfall incidence at the time culture, machinery available, availability of resources, etc. Due to the dynamism of these aspects, some factors inherent to the production chain are influenced, being the stability of the machines and the quality of the operation being mentioned. Adverse climate and soil conditions can drastically influence the quality of the operation and the stability of the tractor, one way of mitigating the damaging effects of these conditions is by adjusting the gauge. The aim was to develop a system that allows the regulation of the distance between the trains of a tractor in an automated way. A prototype of a system with automatic axle gauge regulation specially designed for application in multifunctional machines has been developed, with a patent application. The system allows the distance control between the wheels of said agricultural equipment to be regulated in an automated manner. In management, automatic control is provided with gauges programmed for crops or adjusted by the operator. The chassis allows to couple in its structure heads with multiple functions. The transverse telescopic beams move on its axis. The MPLAB IDE v8.92 Softwares made by MICROCHIP, was the development environment of the PIC microchips programming used in the programming of PIC18F4550 and run as a 64-bit application in Microsoft Windows. For the command of the prototype was used Android Studio to develop the program in Java language, making it easier to use on Android phones allowing the prototype command via Bluetooth.